ANALYSIS OF THE DIFFICULTY OF FIFTH-SEMESTER MIDWIFERY STUDENTS IN LEARNING ENGLISH - Pipit Rahayu; Eripuddin Eripuddin; Ida Safzatul Iffa Halim (English Study Program University of Pasir Pengaraian, 2025)
This research aims to discuss the difficulties faced by fifth-semester students of the midwifery study program at Pasir Pengaraian University in learning English. The method used is qualitative descriptive research, which involves data collection through questionnaires and interviews with students. The research results show that 54,2% of students have difficulty understanding pronunciation in English, and 41,7% often make mistakes when translating sentences from English to Indonesian. In addition, 70.8% of students admitted that they did not understand the homonym difference, and 50% had Difficulty writing correctly. This research highlights the importance of teaching English that focuses on translation skills and contextual understanding to improve students' communication skills. Thus, this research provides valuable insight into developing English courses in the midwifery study program.